Comparative Study of Economic Evaluation of PSC Cost Recovery and PSC Gross Split Scheme for Expiry Block, Case Study Field A in Sumatera - Yulia, Prayang Sunny; Sidqi, Adji Nadzif; Irham, Syamsul; Maulani, Mustamina; Wijayanti, Puri (Journal of Earth Energy Engineering, 2023)
In August 2021, there was an alteration in the production-sharing contract for Field A, which is located at Rokan Block, Riau Province. The methods that were applied were waterflood and artificial lift by using an Electrical Submersible Pump (ESP). This block is an expiry block, whereas a new block is due to contract expiry from the previous contractor. The contract previously used was a Production Sharing Contract (PSC) Cost Recovery, which changed to PSC Gross Split. This contract comparison aims to synergistically evaluate the comparison of the two economic models and also to determine a more efficient and appropriate scheme to be applied to field A, as well as to analyze the parameters that can affect the economic indicators. The results of the economic analysis that has been carried out show that the PSC Gross Split scheme is better than the PSC Cost Recovery scheme. The NPV of the PSC Gross Split scheme for 30 wells was $37,903,000, and the PSC Cost Recovery scheme for 30 wells was $13,850,000. From 30 wells, the result decided on the A6 Well, which the NPV of A6 Well has the best NPV for both schemes based on the contractor's point of view, $494,000 for the PSC Cost Recovery, and $ 1,380,000 for the PSC Gross Split. The Pay Out Time (POT) is derived as well from A6 Well for both schemes, which is 1.39 years for PSC Cost Recovery and 1.2 years for PSC Gross Split. The Interest Rate of Return (IRR) of PSC Cost Recovery is 146% on the A19 Well, and for PSC Gross Split is 408% on the A4 Well. The sensitivity analysis that has been carried out shows that the parameters of the amount of oil production and the price of oil have a significant effect on both schemes.